Given the function:
![f\mleft(x\mright)=\mleft(x+2\mright)\mleft(x-4\mright)](https://img.qammunity.org/2023/formulas/mathematics/college/7s9dwybfr42yfe4cvb2zean9egloeo13th.png)
You can rewrite it as follows:
![y=\mleft(x+2\mright)\mleft(x-4\mright)](https://img.qammunity.org/2023/formulas/mathematics/college/4viptt2ul8aguwg9wy708ywuemr56vtrbg.png)
You need to remember that the y-value is zero when the function intersects the x-axis. Then, you need to make it equal to zero, in order to find the x-intercepts:
![\begin{gathered} 0=\mleft(x+2\mright)\mleft(x-4\mright) \\ (x+2)(x-4)=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5sd0cpjocpvzk85rupgcsx656nq0ueexcm.png)
Solving for "x", you get these two values:
![\begin{gathered} x+2=0\Rightarrow x_1=-2 \\ \\ x-4=0\Rightarrow x_2=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/n3l3dqwdr5ak1ob1ok7etpx5mezwwmw12p.png)
In order to find the vertex, you can follow these steps:
1. Find the x-coordinate of the vertex with this formula:
![x=-(b)/(2a)](https://img.qammunity.org/2023/formulas/mathematics/college/7gr846x3106wifbv8ib3mo7x3lghpti0f2.png)
To find the value of "a" and "b", you need to multiply the binomials of the equation using the FOIL Method. This states that:
![\mleft(a+b\mright)\mleft(c+d\mright)=ac+ad+bc+bd](https://img.qammunity.org/2023/formulas/mathematics/college/ovf1vcmzbcje770sni8pcylweyg9inbu5g.png)
Then, in this case, you get:
![\begin{gathered} y=(x)(x)-(x)(4)+(2)(x)-(2)(4) \\ y=x^2-4x+2x-8 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qkw1zoszfv8vejnnbqm8w7tfdbh1q7cobs.png)
Add the like terms:
![y=x^2-2x-8](https://img.qammunity.org/2023/formulas/mathematics/college/jvtfjtlgxwislb13wd7nufhufxgld1iy2p.png)
Notice that, in this case:
![\begin{gathered} a=1 \\ b=-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/wjlgkruyy9dlub3eax0ipv01p9fkaddpeu.png)
Then, you can substitute values into the formula and find the x-coordinate of the vertex of the parabola:
![x=-((-2))/(2\cdot1)=-((-2))/(2)=1](https://img.qammunity.org/2023/formulas/mathematics/college/avjk2wwha3isheak2nlktxbtcc8zxomel9.png)
2. Substitute that value of "x" into the function and then evaluate, in order to find the y-coordinate of the vertex:
![\begin{gathered} y=x^2-2x-8 \\ y=(1)^2-2(1)-8 \\ y=1-2-8 \\ y=-9 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/23wgybnlto4tl8hmrinzp693coneu9wh50.png)
Therefore, the vertex of the parabola is:
![(1,-9)](https://img.qammunity.org/2023/formulas/mathematics/college/ufg4lecixhgt9d379axd4ov5drtyiy1gwt.png)
Knowing the x-intercepts and the vertex of the parabola, you can graph it.
Hence, the answer is: